Comparing L2 Teachers' Practices With Learners' Perceptions of English Pronunciation Teaching - Michael Burri (Universidad Nacional de Colombia, 2023)
The present study compares the pronunciation practices of three English instructors (two teaching in Australia and one in Japan) with the perceptions of their learners (n = 49). A student questionnaire, semi-structured teacher interviews, and classroom observations were used to collect data. The findings show that the learners strongly desire to be taught and improve their pronunciation, and the teachers' provision of oral corrective feedback meets the students' preferences. However, the use of primarily controlled (teacher-centred) techniques and subsequent lack of opportunities for communicative pronunciation practice suggest some incongruity between teachers' practices and students' perceptions. Factors such as the curriculum, instructors' beliefs about second language learning, and their confidence play a role in this discrepancy.